Are we ready to collaborate? The interprofessional collaborative competencies of healthcare professionals in the Global South context - Soemantri, Diantha; Findyartini, Ardi; Werdhani, Retno Asti; Koesnoe, Sukamto; Dahlia, Debie (Frontiers in Medicine, 2022)
Background: Current evidence of interprofessional collaboration suggests the importance of measuring and identifying the current state of the health professions’ interprofessional competencies. Therefore, this study was aimed at measuring the interprofessional competencies of health professionals in the Global South context using the validated CICS29. Methods: This was a cross-sectional study involving 300 healthcare professionals of a newly established teaching hospital. Prior to the measurement of interprofessional competencies, the 29-items CICS29, which has been translated into Indonesian language, was revalidated using a confirmatory factor analysis (CFA). The 29 items of CICS29 were grouped into six subscales and each item was measured using a 5-point Likert scale. Data on gender, age, type of profession and the length of working experience was also collected to identify whether discernible differences between grouping variables exists. Results: Prior to measuring the interprofessional competencies, the validity of the instrument was established. Based on the CFA, the same six-factor model was found in the current study. The Indonesian CICS29 was reliable, with Cronbach alpha values of 0.921 for the whole instrument and that of each subscale ranged between 0.656 to 0.726. The mean total score of CICS29 was 128.53 (out of 145), ranged from 123 to 133.40 obtained by pharmacists and dentists respectively. No significant differences of CICS29 scores were found between grouping variables. Conclusions: The current study has revealed relatively good interprofessional competencies of healthcare professionals working in a newly established teaching hospital in the Global South healthcare context. Measuring the interprofessional competencies serves as baseline for further intervention to nurture and maintain collaborative practice. In addition, the current study has further proven the cross-cultural validity of CICS29, thus appropriate to be utilized in different setting and context.